Novel SiO2‐Supported Chromocene and Vanadium Bimetallic Catalysts Producing Bimodal Polyethylene. Issue 13 (9th June 2020) - Wang, Kai; Zhang, Rui; Ren, He; Zhao, Ning; Jin, Yulong; He, Xuelian; Liu, Boping
Abstract: Polyethylene (PE) with bimodal molecular weight distribution has intrigued researchers because of its significant processability and mechanical properties. Novel SiO2 ‐supported chromocene (S‐9)/vanadium (V) bimetallic catalysts utilizing the different hydrogen response for producing bimodal PE are successfully synthesized and studied systematically. The catalysts are prepared through using the residual hydroxyl groups on the surface of SiO2 ‐supported vanadium catalyst to introduce chromocene. Both of the low molecular weight (MW) fraction and the high MW fraction can be controlled through adjusting the loading of bimetallic active centers. The bimetallic catalysts also show good 1‐hexene incorporation ability in ethylene/1‐hexene copolymerization. Abstract : A novel SiO2 ‐supported chromocene (S‐9)/vanadium (V) bimetallic catalyst system capable of making bimodal polyethylene is successfully developed. Both of the low molecular weight (MW) fraction and the high MW fraction can be controlled through adjusting the metal loading of each metallic active center. The bimetallic catalyst also shows high activity and 1‐hexene incorporation ability in ethylene/1‐hexene copolymerization.